A REVIEW OF FOOD SECURITY IN THE ERA OF TECHNOLOGICAL EDUCATION MODERN - Kamilah, Hasilatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Food security is one of the enormous issues in responding to worldwide challenges in today's technological environment. This article aims to provide a detailed overview and in-depth objectives regarding the relationship between food security and technological progress, as well as new perspectives to address these challenges. The rise of technological innovations such as US precision agriculture, biofortification, and big data is creating new opportunities to improve productivity and sustainability in the food system. While technology opens the door to new solutions, challenges such as the digital divide and environmental sustainability must also be addressed. This article highlights how important social inclusion is in technological development so that all levels of society, including marginalised groups, can also enjoy its benefits fairly and equitably. Furthermore, a sustainable approach is needed to ensure that technology benefits the current generation and considers future generations' needs. This article also aims to enhance our understanding of how technology can effectively address food-related global challenges by analysing the complex relationship between modern technology and food security. The information presented in this article is expected to contribute to developing more effective policies and sustainable Strategies to ensure food sufficient for the world's population in the future.